Analisis Tingkat Pengetahuan Mitigasi Bencana Banjir pada Siswa Berkebutuhan Khusus di SLB X Kota Semarang - M. Aulia Farhan Akmal (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The frequency of floods in Central Java is the highest with 54 incidents. This study aims to analyze what factors are associated with flood disaster mitigation knowledge of students with special needs in SLB X in Semarang City. This research design uses cross sectional. The population in this study amounted to 32 respondents with total sampling technique so that the number of samples in this study was 32 respondents. The results showed that age (p=0.02) and education level (p=0.004) were related to the level of flood mitigation knowledge.